ANALYSIS OF RESEARCH SKILLS FOR HIGH SCHOOL STUDENTS ON BIOLOGY LEARNING - Moh Sarjana; Elzha Yulianingsih Haditia; Na’ilah Zhafirah; Evi Roviati (Jurnal Ilmu Pendidikan Indonesia, 2025)
Abstract: Research skills are important for students because they can help identify problems, collect sources of information, channel resources for the quality and relevance of research and produce effective solutions to problem solving. This study was conducted in three different schools in the city and district of Cirebon. The three schools include SMA Negeri 1 Sumber, SMA Negeri 1 Ciwaringin and MAN 2 Kota Cirebon. The research method used is descriptive qualitative. The results of this study indicate that students' research skills in Cirebon need to be improved. It is recommended for SMA/MA Cirebon teachers to apply active and collaborative learning methods, such as project-based learning or laboratory experiments, with the aim of improving students' research skills. It is hoped that these steps will contribute to the development of students' critical and analytical thinking skills, and foster independence in research. Keywords: Research skills, Laboratory, Critical thinking skills, Problem solving